The Case against Land Application of Sewage Sludge Pathogens - Maureen Reilly (Canadian Journal of Infectious Diseases)
There is currently a public debate about whether health, agricultural and environmental authorities should continue to allow sewage sludge to be spread on farmland. Some of the concern in the debate is about the pathogen content of sewage sludge. This concern was heightened by the tragedy at Walkerton where Eschericha coli 0157:H7 and other pathogens contaminated the drinking water supply of this Ontario town. The Canadian public were reminded how vulnerable they can be to disease when agricultural practices ajoin population centres without adequate health and environmental controls.